Cladamide: a new ceramide from the endophytic fungus Cladosporium cladosporioides. Issue 7 (3rd April 2023) - Sallam, Amal; El-Metwally, Mohamed; Sabry, Mohamed A.; Elsbaey, Marwa
Abstract: A new ceramide, named cladamide (1 ), in addition to cinnamic acid (2 ), para -coumaric acid (3 ), stigmasterol-3- O - β -D-glucoside (4 ), and uracil (5 ), was isolated from the white beans culture of Cladosporium cladosporioides, a marine-derived endohpytic fungus isolated from the leaves of the mangrove, Avicennia marina (Forssk.) Vierh. Structure elucidation of compound 1 was established on the basis of extensive 1D and 2D NMR spectroscopic techniques in combination with HR-ESI-MS. The ability of the isolated compounds to inhibit acetylcholine esterase was evaluated. Compound 3 showed the highest acetylcholine esterase inhibitory activity (IC50 = 0.057 ± 0.003 µM), followed by compound 4 (IC50 = 0.068 ± 0.003 µM) and compound 1 (IC50 = 0.099 ± 0.005 µM) compared to donepezil, the positive control, (IC50 = 0.044 ± 0.002 µM). Compounds 2 and 5 showed lower activity (IC50 = 0.182 ± 0.009 and 0.236 ± 0.012 µM, respectively). The results were further validated by molecular docking study. Graphical Abstract: UF0001